Improved charge storage performance of a layered Mo1.33C MXene/MoS2/graphene nanocomposite. Issue 23 (7th October 2021) - EL Ghazaly, Ahmed; Méndez-Romero, Ulises A.; Halim, Joseph; Nestor Tseng, Eric; O. Å. Person, Per; Ahmed, Bilal; Wang, Ergang; Rosen, Johanna
Abstract : Felxiable Mo1.33 C i -MXene/MoS2 /graphene (MOMG) nanocomposite electrode delivers volumetric capacitance up to 1600 F cm −3 in sulphric acid electolyte. Abstract : The construction of nanocomposite electrodes based on 2D materials is an efficient route for property enrichment and for exploitation of constituent 2D materials. Herein, a flexible Mo1.33 C i -MXene/MoS2 /graphene (MOMG) composite electrode is constructed, utilizing an environment-friendly method for high-quality graphene and MoS2 synthesis. The presence of graphene and MoS2 between MXene sheets limits the commonly observed restacking, increases the interlayer spacing, and facilitates the ionic and electronic conduction. The as-prepared MOMG electrode delivers a volumetric capacitance of 1600 F cm −3 (450 F g −1 ) at the scan rate of 2 mV s −1 and retains 96% of the initial capacitance after 15 000 charge/discharge cycles (10 A g −1 ). The current work demonstrates that the construction of nanocomposite electrodes is a promising route towards property enhancement for energy storage applications.